Risk factors associated with leptospirosis in swine in state of Pernambuco, Brazil - Santos,Cleber Vinicius Brito dos (2019)
ABSTRACT: Leptospirosis is a major public health threat, and swine are one of the most important reservoirs and sources of Leptospira infection for man. The aim of this study was to investigate the epidemiological situation of leptospirosis in swine in the state of Pernambuco, Brazil. Blood samples from 265 swine were collected and tested by the microscopic agglutination test (MAT), and an epidemiological form containing questions about animal production characteristics, reproductive management, and sanitary and hygiene aspects of the herd was applied to evaluate infection risk factors. The data were analyzed by means of a logistic regression model. An occurrence of 53.1% (143/265) of swine positives to Leptospira spp. was observed. The most commons serovars were Icterohaemorrhagiae (39.1%), Pomona (25.9%), and Shermani (14.0%). Factors associated with the infection were stagnant water source (p = 0.034, odds ratio - OR = 2.29; confidence interval of 95% - 95%CI 1.06-4.93), farms where the healthy animals are bred with sick ones (OR = 1.69; 95%CI 1.04-2.75), and the properties with flooded areas (OR = 1.65; 95%CI 1.01-2.68). The risk factors found in this study played an important role in the agent dissemination and should be avoided in a way to control the disease in the herds studied.